Energy and regional integration? The Democratic Republic of Congo's position in the southern African power pool - (:unkn) unknown (My University, 2013)
Panel A new scramble for Africa? The rush for energy resources southwards of the Sahara, mod. Sören Scholvin, Georg Strüver http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=1800
Keywords: African Research